La strumentazione UAV nel rilievo e nella modellazione tridimensionale di un sito archeologico - Piani, Paola (Archeomatica, 2013)
Survey and 3d modelling of an archaeological site through UAV equipment The technological solutions made today available by the disciplines of the modern Geomatic, offer very interesting opportunities in the field of Cultural Heritage survey. For this study, the archaeological site detected by photogrammetry from UAV system is the medieval castle of Poggio alla Regina in the town of Pian di Scò (AR) Italy. The objectives of the research were: the production of a photographic coverage of the excavation, which is useful to create a detailed mapping and a georeferenced visual contextualization of entities to the ground and the generation of 3d models of the area, on which it was possible to make metric measurements.